The progress of research on the application of redox nanomaterials in disease therapy - Shi, Xiaolu; Tian, Ye; Zhai, Shaobo; Liu, Yang; Chu, Shunli; Xiong, Zhengrong (Frontiers in Chemistry, 2023)
Redox imbalance can trigger cell dysfunction and damage and plays a vital role in the origin and progression of many diseases. Maintaining the balance between oxidants and antioxidants in vivo is a complicated and arduous task, leading to ongoing research into the construction of redox nanomaterials. Nanodrug platforms with redox characteristics can not only reduce the adverse effects of oxidative stress on tissues by removing excess oxidants from the body but also have multienzyme-like activity, which can play a cytotoxic role in tumor tissues through the catalytic oxidation of their substrates to produce harmful reactive oxygen species such as hydroxyl radicals. In this review, various redox nanomaterials currently used in disease therapy are discussed, emphasizing the treatment methods and their applications in tumors and other human tissues. Finally, the limitations of the current clinical application of redox nanomaterials are considered.